2023
DOI: 10.1037/per0000574
|View full text |Cite
|
Sign up to set email alerts
|

Child versus adolescent borderline personality disorder traits: Frequency, psychosocial correlates, and observed mother–child interactions.

Abstract: Research has established the diagnostic validity of borderline personality disorder (BPD) in adolescence. The roots of BPD often lie in childhood; however, significantly less is known about the presence and correlates of BPD traits in school-age children and whether these are comparable with those observed in adolescents. Trained psychologists administered the Childhood Interview for Borderline Personality Disorder in a cohort of 14-year-old adolescents (n = 76) and a cohort of 9-year-old children (n = 70). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…For adolescents with BPD traits, in our sample mainly characterized by impulsivity, self-harm/suicidality and uncontrollable anger [ 48 ], adaptive co-regulatory processes in behavior and physiology during social interaction could function as important stabilizers supporting adolescent self-regulatory systems. In our community sample, mothers and adolescents showed a constant decrease in cortisol on average.…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents with BPD traits, in our sample mainly characterized by impulsivity, self-harm/suicidality and uncontrollable anger [ 48 ], adaptive co-regulatory processes in behavior and physiology during social interaction could function as important stabilizers supporting adolescent self-regulatory systems. In our community sample, mothers and adolescents showed a constant decrease in cortisol on average.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst overall collaboration as a marker for dyadic behavior during conflict discussions did not predict adolescent BPD traits in a high-risk community sample [60], it contributed to a more secure attachment profile in the clinical sample of young adults [54]. Fleck et al [34] observed interactions in two community samples. At age 9, they found less maternal structuring and more child withdrawal during a conflict discussion task to be associated with BPD traits, but no relations during a fun day planning task.…”
Section: Caregiver-child Interactions and Bpdmentioning
confidence: 98%
“…This seems to be especially relevant in stressful contexts (e.g. [34], when problems with emotion regulation would become noticeable. There is also first evidence that positive parental and dyadic behavior might mitigate the development of the disorder [39,92].…”
Section: Caregiver-child Interactions and Bpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Another significant underlying psychopathology is personality disorder, especially borderline personality disorder (BPD) and other cluster B entities. Although the diagnosis of BPD in children and adolescents is controversial, more and more clinicians are using this term to explain recurring DSH among adolescents, especially girls [32].…”
Section: Ideation-to-action and Imminent Risk Frameworkmentioning
confidence: 99%